A clinical study of cardiac rhythm disturbance in patients with chronic obstructive pulmonary disease using 24 hour Holter monitoring - Dabadghao, Varsha S.; Patil, Rajsinh; Sharma, Suresh K.; Kakrani, Arjun L. (International Journal of Research in Medical Sciences, 2016)
Background: Chronic obstructive pulmonary disease (COPD) has been defined by GOLD (guidelines for obstructive lung disease) as a disease state characterised by airflow limitation that is not fully reversible, with FEV1/FVC <70%. COPD increases the risk of cardiac arrhythmias. In acute exacerbation and also in stable COPD, it has been found that arrhythmias are associated with more mortality. Holter monitoring enhances the possibility of observing cardiac rhythm during symptoms and can detect arrhythmias in asymptomatic patients. The aim of this study was to estimate the prevalence and types of arrhythmias in COPD patients and to correlate them with severity. Methods: This was a cross-sectional prevalence, analytical study conducted for a period of two years. Fifty cases with sign and symptoms of COPD diagnosed on pulmonary function tests (PFT) as per GOLD’s criteria were included. Diagnosis of arrhythmia in COPD was on the basis of Holter monitoring. 24 hour Holter monitoring was done with Release 2.9 Digitrak XT Philips. The data was analysed using chi square test. Results: The most common arrhythmias on Holter monitoring were atrial pair and atrial premature beats which were present in 29 (58%) and 25 (50%) patients respectively, atrial run (32%), ventricular premature beats (32%), ventricular couplets (30%), ventricular triplets (24%), ventricular trigeminy (24%) and ventricular run (22%). Atrial fibrillation was noted in 7 patients (14%). Conclusions: The significant presence of supraventricular and ventricular arrhythmias in patients with COPD were detected on Holter monitoring.